Evaluasi Fisik Body lotion dari Bubur Rumput Laut Ulva lactuca dan Gel Aloe vera - Inas Almira; Insan Fauzy; Moehammad Pramana Hussein; Rena Puji Rahayu; Riva Regina Nabilah; St. Nurul Fadilah; Rifki Prayoga Aditya; Afifah Nurazizatul Hasanah; Ginanjar Pratama; Meliyantika, Rindi; Rostiati, Aini (Faculty of Science and Technology University Ibrahimy, 2023)
Ulva lactuca contains various bioactive compounds, and has been developed by many recent researchers into cosmetic products, especially for skin. In addition, other types of plants that can be used for cosmetics, namely Aloe vera which has lots of nutrients and vitamins for the skin. This study aims to obtain the best body lotion formulation from U. lactuca and A. vera based on thwphysical evaluation. The process of making body lotion consists of two stages, namely the oil phase and the water phase, then homogenized at 70-75°C. The formulation in the study varied with the addition of U. lactuca and A. vera with a ratio of 1:2 (F1), 1:1 (F2), 2:1 (F3) and F0 as a control treatment. The body lotion formulation with a ratio of 1:2 (F2) has a good moisture level for the skin and a pH value that is suitable for the skin, and all treatments have spreadability that meets the standards. All treatments have an oil-in-water emulsion type. In centrifugal testing no phase is formed. The organoleptic test results for all products ranged from moderate to like. The results of this study indicate that the F1 formulation is the best formulation of all treatments because it has a good pH and moisture value for the skin.